Making a skirt: including designs, patterns, and adjustments - Pivnick, Esther, 1913- (New York, Hearthside Press, 1967)
Includes chapters on basic pattern design; style variations including back wraps, flares and pleated skirts; culottes; grading; procedures from a sketch to a finished skirt; and information on such aspects as belts, pockets, and zippers.
Keywords: Skirts; Skirts; Dressmaking